DIVERSIFICATION OF FINANCIAL FLOWS IN THE PROMOTION OF ECONOMIC DEVELOPMENT - Paentko Т.В. (Journal of Information Technologies in Education (ITE), 2014)
The article is devoted to the problems of stimulating economic development. International experience of state regulation of economic development is studied. The optimal financing of economic development at the expense of economic entities and the state is justified. Applying of new software to quickly processing and interpreting data, which substantially reduces the time for making financial decisions and reduces the risk of errors. Prospects for further research study identified diversification of financial flows for various real economics industries through the application of information technology. To stimulate the development of the real economy to direct budget investments in terms of growth, which will provide impetus for economic development? In order to overcome the negative impact of institutional deformations in expenditure propose to use the mechanism of diversification of financial flows. Its essence is that the priorities of economic activities funded under the co-financing: budget grant and equity investors. To achieve sustainable GDP growth state should maintain the ratio of budget investments and investments for its own account enterprises in a certain percentage in the form of budget investments and investments on their own businesses.